Development of Value Paradigm in Management - G. V. Serebryakova (Управление)
The article describes the need of formation and use of the organizational and economic mechanisms promoting strengthening of spiritual and moral components in the administrative environment. Besides, the special attention is paid to a question of interaction in the company which lays the foundation of valuable management of social and economic systems. Article is written on the basis of materials, received from the research work within the framework of the state task of the Ministry of education and science of the Russian Federation.